Practice of disciplinary methods and factors associated with belief for physical punishment among Malaysian parents: findings from NHMS 2016 - Ganapathy, Shubash Shander; Sooryanarayana, Rajini; Mohammad, Nik Mazlina; Abdul Manaf, Rosliza (SAGE Publications, 2022)
The belief in the effectiveness of physical punishment is an important predictor for its use. The objectives of this study was to describe the factors associated with the belief for physical punishment toward children 1 to 5 years of age among Malaysian parents. Data was collected as part of the Malaysian National Health and Morbidity Survey (NHMS) 2016. The respondents were asked if they believed that physical punishment is needed to raise a child properly. A total of 60.0% of Malaysian parents believed in the need for physical punishment, with 54.3% practising it. Parents who believed in physical punishment had more than 2 times a higher likelihood of practising it (odds ratio 2.57) than those who did not. Parents need to be taught to respond positively to children’s behavior and anger management strategies in difficult parenting situations.